ASSESSMENT OF DRUG-DRUG INTERACTION IN GERIATRIC IN-PATIENTS OF A TERTIARY CARE TEACHING HOSPITAL: A CROSS -SECTIONAL STUDY. - Dr Raghavendra Belavatagi; Dr Anusha S J; Dr Venkatesh K M (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Objective: This study evaluated the prevalence and characteristics of potential drug-drug interactions (pDDIs) among geriatric inpatients in a tertiary care hospital.Methods: A cross-sectional study was conducted over six months including patients aged 65 years and above prescribed two or more medications. Medication records were reviewed using electronic interaction databases Micromedex to identify pDDIs. Descriptive statistics summarized interaction frequencies and severity, while chi-square tests assessed associations between demographics and interaction occurrence.Results: Among 220 patients, a total of 519 drug interactions were identified from 620 prescriptions, indicating a high prevalence of 85.91%. Moderate and major interactions comprised 38.05% and 31.14%, respectively. Age was significantly associated with interaction frequency, particularly in patients aged 60–79 years (p=0.002). Common interacting drugs included anticoagulants, cardiovascular agents, CNS depressants, and antidiabetics.Conclusion: This study highlights a substantial burden of drug interactions in elderly patients, underscoring the need for vigilant monitoring, tailored pharmacotherapy, and interdisciplinary management. The use of electronic screening tools and pharmacist involvement may reduce adverse outcomes and improve therapeutic safety in this vulnerable population.